Inside the Queue - Erik T. Verhoef (Tinbergen Institute, 2002)
This paper develops a continuous-time -continuous-place economic model of road trafficcongestion with a bottleneck, based on car-following theory. The model integrates twoarchetype congestion technologies used in the economics literature: 'static flow congestion',originating in the works of Pigou, and 'dynamic bottleneck congestion', pioneered byVickrey. Because a closed-form analytical solution of the formal model does not exist, itsbehaviour is explored using a simulation model. In a setting with endogenous departure timechoice and with a bottleneck along the route, it is shown that 'hypercongestion' can arise as adynamic -transitional and local- equilibrium phenomenon. Also dynamic toll schedules areexplored. It is found that a toll rule based on an intuitive dynamic and space-varyinggeneralization of the standard Pigouvian tax rule can hardly be improved upon. A naiveapplication of a toll schedule based on Vickrey 's bottleneck model, in contrast, appears toperform much worse and actually even reduces welfare in the numerical model.
Keywords: R41; R48; D62; 330; congestion; road pricing; networks; Straßenverkehr; Verkehrsstau; Bottleneck; Dynamisches Modell; Straßenbenutzungsgebühr; Theorie